Design and evaluation of algorithms for obtaining objective trustworthiness on acquaintances in P2P overlay networks. (1st January 2011) - Sawamura, Soichi; Barolli, Admir; Aikebaier, Ailixier; Takizawa, Makoto; Enokido, Tomoya
In fully distributed P2P overlay networks, each peer has to obtain information on objects distributed through communicating with its acquaintances. An acquaintance might hold obsolete information due to the propagation delay and faults of peers. Hence, a peer has to collect information only from trustworthy acquaintances. The subjective trustworthiness shows how much a peer trusts its acquaintance. The objective trustworthiness indicates how much other peers trust the acquaintance. We discuss three algorithms to calculate the objective trustworthiness. The algorithm OT1 shows a type of flooding algorithm. A peer sends request messages only to the acquaintances to reduce the number of messages in the algorithms OT2 and OT3. Furthermore, the peer p s sends messages to only acquaintances which the peer p s can trust in OT3. Then, the peer p s receives the subjective trustworthiness on the acquaintance from the acquaintance p u . The peer p s obtains the average value of the subjective trustworthiness collected as the objective trustworthiness. We evaluate the three algorithms in terms of how correct objective trustworthiness can be obtained by the algorithms.